(3TQM GdCdHGH aj Yde GdEYQGHs - (3LeGd GdOjf YHO Gddg Hf eMeO Hf CMeO GdMSjfj GdfjSCHhQj GdeYQha H` GdfbQI cGQs; (3eMeO Hf eMeO Hf CMeO, JGL GdOjf GdCSaQGjjfj,J (B684 (3g` s ((3Ydj Hf fhQGdOjf Hf Ndjd HGHG eMeO TGg Hf Ydj HGdj s)
(3ChdgG (B:s
(3hHYO, aEf dH GdCdHGH aj Yde GdEYQGH dG jNai YfO Phj GdCdHGH Cfg cKjQ GdahGFO s
(3BNQgG (B:s
(3hjdMb HgG gGA GdScJ dRjGOI GdEfcGQ HNdGa GdeJPcQ aEfg dG jbUO Gdhba hEfeG YQV dg eG ChLH bWY cdGeg ef GdfSjGf, MQQg s
(3fSNI KGdKI JJab ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3ChQGbgG GdChdi HNW eZGjQ hHChdgG hba eDQN SfI (B1232s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs